Into that forest - Nowra, Louis 1950- (Egmont, 2013)
We were lost, and the only thing that could help us were the tiger. The more I looked at its black eyes, the more I seen kindness, and I knew it were saying to us, Come, I'll take you home. This is the story of two girls lost in the Tasmanian bush, saved and raised by two Tasmanian tigers